The Role of Family as a Channel of Intergenerational Transmission of Volunteer Traditions in Contemporary Russia - Irina Mersianova; Dmitri Malakhov; Natalya Ivanova (Journal of Economic Sociology, 2019)
The paper focuses on the role of family in forming the consistency of volunteering traditions in contemporary Russia. The paper investigated the correlation between parental volunteering and the current volunteering of their children. International studies indicate that family impact on children’s attitude towards volunteering is a significant channel of intergenerational transmission of prosocial behavioral patterns. One of the viewpoints that draws on the social learning theory (A. Bandura), posits that children model their prosocial behavior, such as volunteering, on the direct example of their parents. Another viewpoint pertaining to the resource theory links the transmission of volunteerism with the transmission of parental social status. Social status transmission can be accompanied by normative pressure since a higher socio-economic status is associated with unpaid voluntary contribution for the benefit of society. The key hypothesis of the research proposes that in Russia, where volunteerism still has not taken root as a sociocultural norm and is not associated with the transmission of social status, the transmission of volunteerism is mostly due to direct family influence and is particularly due to the influence of parental volunteering. The paper presents the results of the All-Russia Representative Survey, which confirm the above hypothesis. Using a linear probability model and the logit model, we show that in Russia, active parental volunteering is likely to be strongly and significantly associated with the respondents’ current volunteering. The results demonstrate stability with the change of the model specification and a set of control variables. The paper has important practical implications for nonprofit organizations on how to engage volunteers of different generations by developing family volunteer programs. Such programs could facilitate early motivation of children to volunteer through direct observation and modeling of parental prosocial behavior.